2013
DOI: 10.1155/2013/186098
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect ofThunbergia laurifolia(Linn.) on Lead Induced Acetylcholinesterase Dysfunction and Cognitive Impairment in Mice

Abstract: Thunbergia laurifolia (linn., TL), a natural phenolic compound, has been reported to have many benefits and medicinal properties. The current study ascertains the total phenolic content present in TL aqueous leaf extract and also examines the antioxidant ability of the extract in preserving acetylcholinesterase (AChE) activity of mice exposed to lead in vivo and in vitro model. Mice were given lead acetate (Pb) in drinking water (1 g/L) together with TL 100 and 200 mg/kg/day. The result showed that Pb induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Another study by Reddy et al, ( 2007 ) reported sensitivity of the cholinergic system to Pb, supported by in vitro studies of 35 PND rat brains using different concentrations of Pb, which showed dose dependent inhibitory actions on the cholinergic system. However, previous reports found that Pb exposure had a direct action on cholinergic neurons causing decrease of AChE coupled with increased ACh (Mansouri et al, 2013 ; Phyu & Tangpong, 2013 ). Pb has a high affinity to free SH groups of AChE and its binding can alter their function, reflecting a possible increase in ACh levels in brain tissues, which is consistent with earlier reports (Reddy et al, 2007 ; Mansouri et al, 2013 ; Basha et al, 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Another study by Reddy et al, ( 2007 ) reported sensitivity of the cholinergic system to Pb, supported by in vitro studies of 35 PND rat brains using different concentrations of Pb, which showed dose dependent inhibitory actions on the cholinergic system. However, previous reports found that Pb exposure had a direct action on cholinergic neurons causing decrease of AChE coupled with increased ACh (Mansouri et al, 2013 ; Phyu & Tangpong, 2013 ). Pb has a high affinity to free SH groups of AChE and its binding can alter their function, reflecting a possible increase in ACh levels in brain tissues, which is consistent with earlier reports (Reddy et al, 2007 ; Mansouri et al, 2013 ; Basha et al, 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Lead (Pb) is known as a highly neurotoxic agent that causes functional and structural abnormalities in the brains [ 131 ]. In addition, Pb induces neurotoxicity in the cerebrum, cerebellum, and medulla oblongata of rat brain.…”
Section: Miscellaneous Activitiesmentioning
confidence: 99%
“…1 It has been widely used as detoxification and antipyretic drug in Thai traditional medicine for centuries 2 and also included in "Thailand National List of Essential Medicines". 3 Modern pharmacological experiments revealed that the TL possessed antioxidant, 4 antiinflammatory, 5 hepatoprotective, 6,7 antidote, 8,9 antitumor 10 and anti-hyperglycemic activities. 11 Previous studies of TL reported that rosmarinic acid (RA) is the major anti-oxidative constituent 12 together with its derivatives caffeic acid (CA).…”
Section: Introductionmentioning
confidence: 99%